PENGARUH PENERAPAN STRATEGI BELAJAR AKTIF TIPE GROUP TO GROUP TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI SMAN 1 V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Yufinda, Amelia - (STKIP PGRI Sumbar, 2014)
Learning biology at SMAN 1 V Koto Kampung Dalam is monotonous. This condition resulted to the studentsâ science learning outcomes are low. One of the reason is the teacher only uses the lecture method during the learning process, so that the students often feel bored because just listening to the explanation from the teacher. To overcome this problem, it is necessary better to apply one way to keep students active and motivated in learning from an active learning strategy into group to group. This research is aimed to determine the effect of the application of active learning strategies with group to group towards learning biology outcomes at XI class of SMAN 1 V Koto Kampung Dalam. This research is an experimental research by using a randomized study design with Posttest Only Control Group Design. The population in this research is all students at XI class of SMAN 1 V Koto Kampung Dalam In academic year 2013/2014. The sampling used is purposive sampling technique, so that XI class IPA4 becomes experimental class and XI class IPA2 as control class. The data in this research is the result of student learning outcomes which includes cognitive, and affective. Data on cognitive obtained by performing final tests while the affective domain is done by non test is fill out the observation. The data is analyzed by using t-test. Based on the results of the final test, the average value obtained cognitive experimental class is 76.11 higher than the control class is 66.44. By t test, t = 4.15 is obtained and table = 1.67. Thus t count> t table, so the hypothesis is accepted. The average value of the affective domain experimental class that 76.47 is higher than the control class is 58.89. By t test, t = 4.15 is obtained and table = 1.67. Thus t count> t table, so the hypothesis is accepted.